The Effect of PLGA Nanoparticles of Nigella sativa Seed Extract on Catalase Level in The Liver Tissues of Type 2 Diabetes Mellitus Rats - oktaviana, pratiwi (Pharmaceutical Journal of Indonesia, 2016)
Background:Nigella sativa (NS), a medicinal plant, has antidiabetic and antioxidant effects via regulating blood glucose and antioxidant defence level. One of the antioxidant defence capacity is catalase (CAT) which prevents oxidative stress in the DM progression via balancing redox state. This enzyme could be increased by Nigella sativa seeds extract (NSE). However, plant-derived product has limited efficacy in clinical trial. Thus one of drug delivery system, PLGA encapsulated nanoparticle, may improve this efficacy. Objectives: The aims of this study were to evaluate CAT level in the liver tissues of male DM Sprague dawley rats after oral administration of NSE 48 mg/kgBW/day (P1), PLGA nanoparticle of NSE 48 mg/kgBW/day (P2), glibenklamide 0,45 mg/kgBW/day (PP), and normal diet without therapy (DN). Methodology: True experimental design post test controlled group, 24 rats were fed by high-fat diet for 40 days and followed by intraperitoneal injection of 35 mg/kgBW STZ. These rats were divided into 4 groups: DN, PP, P1, and P2 respectively. Results: Thymoquinone which possesses antioxidant effect was identified by qualitative phytochemical evaluation. PLGA nanoparticle was prepared from nanoprecipitation. The oral administration of PLGA nanoparticle NSE for 26 days to DM rats lowered fasting blood glucose (FPG) (66,67%) better than P1, PP, and DN. The PLGA nanoparticle of NSE did not significantly increased the CAT level in the liver tissues of DM rats (analyzes Oneway-ANOVA p = 0.872). However, the mean of CAT level in the liver tissues of DM rats was higher in group P2 compared to those in the other group. Conclusion: These results exhibited antidiabetic and antioxidant effects of PLGA nanoparticle NSE in term of fasting blood glucose level and CAT level in liver tissues. Key words:Nigella sativa,PLGA Nanoparticle, Catalase